Organizational citizenship behaviour pada karyawan: Bagaimana peranan persepsi budaya organisasi dan komitmen afektif? - Mulyami Choirunnisa; Diah Sofiah; Yanto Prasetyo (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between perceptions of organizational culture and affective commitment with organizational citizenship behavior in employees. This research is a type of quantitative research using correlational research. Subject selection is based on the entire population of employees of PT. Perkebunan Nusantara XI (Head Office) with a total of 60 employees. The data analysis technique used in this research is multiple regression analysis. The results obtained based on the results of the simultaneous correlation regression coefficient in multiple regression analysis were obtained at 11.556 with a significance of 0.000 (p <0.01). This means that there is a very significant relationship between perceptions of organizational culture and affective commitment to organizational citizenship behavior. The higher the perception of organizational culture and affective commitment, the higher the organizational citizenship behavior of PT. Perkebunan Nusantara XI (Head Office) employees. Keywords: Affective Commitment; Employees; Organizational Citizenship Behaviour; Perceptions of Organizational Culture. Abstrak Penelitian ini bertujuan untuk mengetahui hubungan persepsi budaya organisasi dan komitmen afektif dengan organizational citizenship behaviour pada Karyawan. Penelitian ini merupakan jenis penelitian kuantitatif dengan menggunakan penelitian korelasional. Pemilihan subjek didasarkan pada keseluruhan populasi karyawan PT. Perkebunan Nusantara XI (Kantor Pusat) dengan jumlah 60 karyawan. Teknik analisis data yang digunakan dalam penelitian ini adalah teknik analisis regresi berganda. Adapun hasil yang diperoleh berdasarkan hasil koefisien regresi korelasi simultan pada analisis regresi berganda didapatkan sebesar 11,556 dengan signifikansi 0.000 (p < 0.01). Artinya terdapat hubungan sangat signifikan antara persepsi budaya organisasi dan komitmen afektif dengan organizational citizenship behaviour. Semakin tinggi persepsi budaya organisasi dan komitmen afektif, semakin tinggi pula organizational citizenship behaviour pada karyawan PT. Perkebunan Nusantara XI (Kantor Pusat). Kata kunci: Karyawan; Komitmen Afektif; Organizational Citizenship Behaviour; Persepsi Budaya Organisasi.